Prevalence of Thrombocytopenia in Dengue Fever Patients - Nida Tabassum Khan; Shabbir Hussain (LifeSciFi, 2021)
Dengue fever (DF) is an intense febrile disease described by abrupt beginning of fever of 3-5 days, intense migraine, myalgia, joint pain, retro-orbital agony, anorexia, gastrointestinal unsettling influences and different levels of thrombocytopenia. Thrombocytopenia has reliably been one of the likely clinical pointers of dengue severity. As our studies revealed that overall prevalence of thrombocytopenia in Dengue is high i.e., 69% from mild to severe. However, since the female to male ratio i.e., 21:79 was unfairly very low to generalize the gender-wise prevalence result. In addition, severity of clinical manifestation of dengue disease were correlated with the respective platelet counts and there was a negative correlation between platelet count and clinical complications indicating that lower the platelet count more are the complications and their respective severity as patients with lower platelet count was found to have higher chances of non-hemorrhagic complications. Further forthcoming investigations are expected to assess the utility of other blood indices in dengue fever so, there is a need to concentrate on the detail hematology profile and comprehend its significance so that the adverse outcomes of this rapidly spreading disease can be controlled to a great extent.